The Impact of Ford Motor Company’s Voluntary Equal Wage Policy on Detroit’s Wage Gap in the 1940s - Lanning, Jonathan A.; Reynolds, C. Lockwood (Journal of Labor Economics, 2022)
We analyze the impact of Ford Motor Company’s compensation practices on the Detroit-area labor market from 1918 to 1947. Previous studies imply that Ford paid race-independent wages, but its Black workers were sorted into undesirable departments. We extend these results using propensity score reweighting of census data and Ford’s records and confirm that Ford paid equal wages. We then develop a search model with discriminatory and equal wage firms to assess the impact of Ford’s policy on the larger labor market. Calibrated simulations suggest that Ford may have reduced the wage gap in southeastern Michigan by as much as 50%.